Analisis Efektivitas Mesin Hot Press Yamamoto 45 Opening Menggunakan Metode Overall Equipment Effectiveness dan Fault Tree Analysis: Analysis of the Effectiveness of the Yamamoto 45-Opening Hot Press Machine Using Overall Equipment Effectiveness and Fault Tree Analysis Methods - Rawan S, Hend; Raliby Al Manan, Oesman; Rosyidi, Muhammad Imron (Borobudur Engineering Review, 2026)
T This thesis entitled "Analysis of the Effectiveness of the Yamamoto 45 Opening Hot Press Machine Using the Overall Equipment Effectiveness and Fault Tree Analysis Methods (Case Study : PT Dharma Satya Nusantara Temanggung)", was written by Hendrawan Saputra, an Industrial Engineering student at the University of Muhammadiyah Magelang. This research was motivated by the high number of downtimes in the period January 2024 - October 2024 reaching a total of 16687 minutes or 278 hours. This study aims to calculate the effectiveness value of the Yamamoto 45 Opening Hot Press machine and determine the factors that cause downtime on the machine. The data used is historical production and maintenance data covering availability, performance, and quality. The results of the Overall Equipment Effectiveness (OEE) calculation show an average value of 75.41%. It can be concluded that it does not meet the international OEE standard according to Nakajima (1988), which is a value above 85%. The results of the Six Big Losses calculation show that the largest losses come from quality defects and rework, with an average value of 18.21%. Fault Tree Analysis (FTA) analysis shows that the dominant factors causing quality defects and rework are minus materials, large press marks, small press marks, and lack of putty. Based on the results of the study, it can be concluded that the decrease in the OEE value is caused by the quality rate which indicates a fairly high percentage of defects. Recommendations for improvement include checking the putty process which must be dry, checking the cleanliness of the material before entering the platten, and the Team leader must check each operator inserting the material into the platten whether it is centered or not. The application of the OEE, Six Big Losses, and FTA methods can help companies systematically calculate a machine's effectiveness, identify dominant losses, and develop improvement recommendations.